Solving the inverse kinematics for robot manipulators using modified electromagnetism-like algorithm with record to record travel - Abed I.A.; Koh S.P.; Sahari K.S.M.; Tiong S.K.; Tan N.M.L. (Maxwell Science Publications, 2023)
A new modification of Electromagnetism-like (EM) algorithm which incorporating the Record-to-Record Travel (RRT) local search algorithm; namely MEMR has been developed to solve the problem of Inverse Kinematics (IK) for a four Degree-of-Freedom (DOF) manipulator. The proposed method is able to generate multiple robot configurations for the IK test performed at different end effect or positions. In addition, the comparison between the proposed MEMR and Genetic Algorithm (GA) was carried out using two mathematical test functions; De Jong and Rastrigin. The tests results show that the proposed MEMR is comparable in performance to GA in terms of both convergence speed and error rate. © Maxwell Scientific Organization, 2014.